The second boundary value problem of riemann's type for bianalytical functions with discontinuous coefficients - Bolottn, L B. (Mathematical Modelling and Analysis, 2004)
The paper is devoted to the investigation of one of the basic boundary value problems of Riemann's type for bianalytical functions with discontinuous coefficients. In the course of work there was made out a constructive method for solution of the problem in a unit circle. There was also found out that the solution of the problem under consideration consists in consequent solutions of two Riemann's boundary value problems for analytical functions in a unit circle. Besides, the example is constructed.Antrasis kraštinis uždavinys Rimano tipo bianalizinėms funkcijoms su trūkiais koeficientaisSantrauka. Darbe sprendžiamas antrasis kraštinis uždavinys Rimano tipo bianalizinėms funkcijoms su trūkiais koeficientais. Parodoma, kad sprendžiamas uždavinys suvedamas į sprendimą dviejų Rimano uždavinių analizinėms funkcijoms su trūkiais koeficientais. Randamos analizinių funkcijų klasės, kuriose gali būti sprendinys. Pateikiamas pavyzdys, iliustruojantis nagrinėjamo uždavinio sprendimo algoritmą.First Published Online: 14 Oct 2010